The International Centre for the Settlement of Investment Dispute (ICSID) Annulment Reform: a Lesson Learned From the World Trade Organization Struggle - Simbolon, Putu George Matthew; Allagan, Tiurma Mangihut Pitta (Indonesian Journal of International Law, 2024)
This article expresses how ICSID can learn from the WTO’s current struggles due to the Appellate Body vacuum. To achieve that, this article consists of three discussions. The first discussions analyze the uncertainties caused by the vagueness of International Investment Law’s (IIL) absolute standards, due to the absence of a multilateral investment treaty. The second discussion expresses the elements of the Multi-Party Interim Arbitration Arrangement (MPIA Arrangement) that shall be taken into account by ICSID. The third discussion provides how the current ICSID annulment mechanism shall be reformed. Those issues are answered through doctrinal research in a prescriptive manner. In the first discussion, the IIL’s absolute standards consisting of Fair and Equitable Treatment (FET) and Full Protection and Security (FPS) have unclear parameters. Such vagueness is caused by the absence of a multilateral investment agreement. The second discussion explains that ICSID shall transpose the MPIA authority to change its member’s national law. This discussion also presents the consistent practice by the WTO Dispute Settlement Body based on the WTO's substantial rules, as a situation doesn’t exist in IIL. Finally, ICSID needs to expand its annulment scope by ensuring the disputing party’s substantial rights. This article expresses that while it is not the IIL’s duty to unify its material norms due to its dynamic nature, it has to ensure that the disputing parties’ substantial and procedural rights are reasonably taken into account.